The Influence of Student Engagement and Teacher Interpersonal Communication on School Well-Being of Students - Ariansyah, Ahmad Berlian; Ahyani, Nur; Indrawati, Sriwahyu (Perkumpulan Program Studi Doktor Pendidikan (PPSDP), 2024)
The objectives of this study were to: 1) Investigate the effects of student engagement and teacher interpersonal communication on school well-being, 2) Analyze the specific impact of teacher interpersonal communication on school well-being, and 3) Evaluate the combined influence of both student engagement and teacher interpersonal communication on school well-being. The study focused on all 12th-grade students at SMK Negeri 4 Palembang, selecting a sample of 87 students from three classes: Class XII Machining, Class XII Computer Network Engineering, and Class XII Modeling and Building Information Design. A probability sampling technique, specifically simple random sampling, was employed. Data collection involved three scales: the School Well-being Scale, the Student Engagement Scale, and the Teacher Interpersonal Communication Scale. The collected data was then analyzed using multiple linear regression with SPSS 26.0. The results revealed that: 1) Both student engagement and teacher interpersonal communication have a significant influence on school well-being at SMK Negeri 4 Palembang, with an F-value of 28.118, exceeding the F-table value of 3.104, and an R-value of 0.633. 2) Student engagement shows a positive and highly significant impact on school well-being, with a t-value of 7.497, surpassing the t-table value of 1.708 (t-count > t-table). 3) Teacher interpersonal communication also has a positive and significant effect on school well-being, with a t-value of 5.258, higher than the t-table value of 1.708 (t-count > t-table).